2007
DOI: 10.1007/s00412-007-0129-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of cohesin and Nipped-B with transcriptionally active regions of the Drosophila melanogaster genome

Abstract: The cohesin complex is a chromosomal component required for sister chromatid cohesion that is conserved from yeast to man. The similarly conserved Nipped-B protein is needed for cohesin to bind to chromosomes. In higher organisms, Nipped-B and cohesin regulate gene expression and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
295
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(316 citation statements)
references
References 62 publications
21
295
0
Order By: Relevance
“…Key roles for cohesin have been shown in a number of cellular processes including DNA repair, 21,22 chromatin modification, 23 DNA condensation 24 and transcriptional regulation in Drosophila, [25][26][27][28] [36][37][38] have demonstrated that the function of Scc2/NIPBL in sister chromatid cohesion is spatially and temporally associated with that of Scc4/MAU2. The C. elegans homolog mau-2 was originally identified for its role in axon guidance 39 and has subsequently been show to have a role in mitotic chromosome segregation.…”
Section: Cdlsmentioning
confidence: 99%
“…Key roles for cohesin have been shown in a number of cellular processes including DNA repair, 21,22 chromatin modification, 23 DNA condensation 24 and transcriptional regulation in Drosophila, [25][26][27][28] [36][37][38] have demonstrated that the function of Scc2/NIPBL in sister chromatid cohesion is spatially and temporally associated with that of Scc4/MAU2. The C. elegans homolog mau-2 was originally identified for its role in axon guidance 39 and has subsequently been show to have a role in mitotic chromosome segregation.…”
Section: Cdlsmentioning
confidence: 99%
“…Furthermore, when transcription is repressed, cohesin can return (Bausch et al 2007). In flies, cohesin binds to the Abd-B homeobox gene in cells in which it is transcribed, but not in cells in which it is silenced (Misulovin et al 2008). These results emphasize the lack of specificity for any particular DNA sequence, but also highlight that cohesin association with DNA is dynamic, depending on transcription.…”
Section: Introductionmentioning
confidence: 85%
“…The chromosomal sites at which cohesin associates with DNA have been mapped by ChIP-chip (chromatin immunoprecipitation followed by hybridization to DNA microarrays) in yeast, flies, and humans (Glynn et al 2004; Lengronne et al 2004;Misulovin et al 2008;Parelho et al 2008;Stedman 2008;Wendt et al 2008) and by in-situ chromosome staining (McGuinness et al 2005;Gomez et al 2007). These studies revealed both similarities as well as disparities in the localization of cohesin proteins among different eukaryotes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations